PENGARUH KESADARAN SOSIAL DAN PRINSIP-PRINSIP TERHADAP KEPERCAYAAN NASABAH di BANK SYARIAH - Sahwa Aulia S; Antong Antong; Halim Usman (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This research aims to explore the influence of Social Awareness and Islamic Principles on Customer Trust in Sharia Banks. By involving a sample of 102 respondents, this research applies structural analysis and measurement models to test hypotheses and check the validity and consistency of the model. The results of the analysis show that Social Awareness has a positive and significant impact on Customer Trust, with the mediating role of Islamic Principles. Islamic Principles have also been proven to make a significant positive contribution to Customer Trust in Sharia Banks. However, there are several aspects that need to be considered in the measurement model, including further evaluation of its validity and reliability. Suggestions for further development include strengthening education on Social Awareness and Islamic Principles, implementing consistent internal policies, increasing customer involvement through social participation programs, reviewing measurement models, and evaluating and improving statistical fit. This research provides useful insights for Islamic banks in improving relationships with customers and strengthening their position as financial institutions that comply with social and Islamic values.